Posterior Fontanelle Sonography: An Acoustic Window into the Neonatal Brain - Correa, Flavia; Enríquez, Goya; Rosselló, José; Lucaya, Javier; Piqueras, Joaquim; Aso, Celestino; Vázquez, Elida; Ortega, Arantxa; Gallart, Alfredo (American Journal of Neuroradiology, 2004)
BACKGROUND AND PURPOSE: Sonographic brain studies are classically performed through the anterior fontanelle, but visualization of posterior supratentorial and infratentorial structures is poor with this approach. Posterior fontanelle sonography is recommended for better assessment of these structures. Our purpose was 1) to determine whether sonography of the brain through the posterior fontanelle (PF) improves visualization of brain lesions when added to the routine anterior fontanelle (AF) approach and 2) to describe standardized PF coronal and sagittal sections.METHODS: In this prospective study (conducted from February 1999 to January 2001), PF sonography was added to AF sonography in 165 consecutive premature neonates with a birth weight of <2000 g. Sonograms were recorded in digital format for re-evaluation at the end of the study. Lesions were grouped as congenital, infectious, hemorrhagic, or hypoxic-ischemic. The χ2 test for paired data and the κ coefficient were used to compare diagnoses with AF alone and diagnoses with AF plus PF.RESULTS: PF sonography was performed in 164 of 165 patients: Results were normal in 86 and abnormal in 78. The single posterior fossa malformation detected in this series was best delineated with the PF approach. PF sonography increased the diagnostic rate of grade II hemorrhage by 32%. Cerebellar hemorrhage (two patients) and cerebellar abscesses (one patient) were diagnosed by using the PF approach. PF sonography did not contribute to the diagnosis of periventricular leukomalacia.CONCLUSION: Study of the neonatal brain with the addition of PF sonography afforded greater accuracy in detecting intraventricular hemorrhage compared with AF sonography alone, especially when the ventricle was not dilated. The PF approach better defines posterior fossa malformations.